The advantages and limitations of human liver models in in vitro toxicology study (International Journal of Biology and Chemistry, 2026)
This review collects and analyses information about modern liver models used in toxicological studies from 2015 to January 2026. Currently, human liver models are increasingly being improved and various approaches being explored, including the selection of different cell types and advanced cultivation methods, to more accurately simulate the in vivo liver environment to replace animal models. These new methods are increasing the complexity of in vitro systems. However, the complex liver models currently available are not yet a complete replacement for animal models and does not have all the characteristics of the liver. Since many models undergo phenotypic changes during prolonged cultivation, this limits their suitability for long-term studies of repeated administration toxicity. Moreover, they have limited suitability, lack of vascularization, labour demanding and expensive. However, compared to early 2D hepatocyte cultures, these modern systems demonstrate significantly improved prediction accuracy and physiological relevance. With continued development, it may be possible to create models capable of tracking the occurrence, progression, and potential reversibility of liver drug toxicity.Key words: liver cells, HepG2, HepaRG, 2D culture, 3D culture, toxicology